Report on First International Workshop on Robotic Surgery in Thoracic Oncology - Veronesi, Giulia; Cerfolio, Robert; Cingolani, Roberto; Rueckert, Jens C.; Soler, Luc; Toker, Alper; Cariboni, Umberto; Bottoni, Edoardo; Fumagalli, Uberto; Melfi, Franca; Milli, Carlo; Novellis, Pierluigi; et al. (Frontiers in Oncology, 2016)
A workshop of experts from France, Germany, Italy and the United States took place at Humanitas Research Hospital Milan, Italy, on 10-11 February 2016, to examine techniques for and applications of robotic surgery to thoracic oncology. The main topics of presentation and discussion were: robotic surgery for lung resection; robot-assisted thymectomy; minimally invasive surgery for esophageal cancer; new developments in computer-assisted surgery and medical applications of robots; the challenge of costs; and future clinical research in robotic thoracic surgery. The following article summarizes the main contributions to the workshop. The Workshop consensus was that, since video-assisted thoracoscopic surgery (VATS) is becoming the mainstream approach to resectable lung cancer in North America and Europe, robotic surgery for thoracic oncology is likely to be embraced by an increasing numbers of thoracic surgeons, since it has technical advantages over VATS, including intuitive movements, tremor filtration, more degrees of manipulative freedom, motion scaling, and high definition stereoscopic vision. These advantages may make robotic surgery more accessible than VATS to trainees and experienced surgeons, and also lead to expanded indications. However the high costs of robotic surgery and absence of tactile feedback remain obstacles to widespread dissemination. A prospective multicentric randomized trial (NCT02804893) to compare robotic and VATS approaches to stage I and II lung cancer will start shortly.